Does Research Reduce Poverty? Assessing the Impacts of Policy-oriented Research in Agriculture - Sumner, A. (2012)
In the current context of the global financial crisis and its aftermath, development resources are likely to be getting scarcer. Resources for development research are too. The set of circumstances generating the resource scarcity is also putting pressure on development gains. More than ever before, every dollar spent on development will have to count towards sustainable poverty reduction, as will every dollar spent on development research. In light of this context this article asks what do we know about the welfare impacts of research in agriculture?.